2019
DOI: 10.11137/2019_1_267_290
|View full text |Cite
|
Sign up to set email alerts
|

Low Cost Geotechnology Applied to Flood Risk Assessment in Coastal Urban Areas in Climate Change Scenarios

Abstract: A elevação do nível médio do mar e a tendência de mais ocorrências de inundações costeiras no mundo são preocupações da comunidade internacional. A compreensão dos perigos, exposição e riscos nas cidades costeiras são importantes para planejar e traçar políticas de adaptação. O objetivo deste artigo foi o de modelar a inundação costeira com tendências à elevação do nível do mar em áreas baixas e planas sob inluência de marés que oferecem riscos ao ambiente urbano, por meio de Remotely Piloted Aircraft (RPA) e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…These spots are justified by the current layout of the city's drainage system, where at high tide times seawater enters the galleries and canals, affecting the interior of the city (Figure 6b and Figure 7). Aguiar et al (2019) found the same structural problem in the urban area of Areia Branca city (approximately 58 km west of Macau city). It is important to mention that the land on which the local cemetery is in the urban area of Macau is one of the few urban sectors in the city not to suffer from tidal flood scenarios.…”
Section: Tidal Flood Hazard and Vulnerability Mapsmentioning
confidence: 58%
“…These spots are justified by the current layout of the city's drainage system, where at high tide times seawater enters the galleries and canals, affecting the interior of the city (Figure 6b and Figure 7). Aguiar et al (2019) found the same structural problem in the urban area of Areia Branca city (approximately 58 km west of Macau city). It is important to mention that the land on which the local cemetery is in the urban area of Macau is one of the few urban sectors in the city not to suffer from tidal flood scenarios.…”
Section: Tidal Flood Hazard and Vulnerability Mapsmentioning
confidence: 58%
“…The geosites present in the other protected areas are also exposed to this type of consequence, enhanced by climate change (Figure 26). Aguiar et al [21] evaluated the risk of tidal inundation due to climate change in the Apodi-Mossoró estuary, sector to the west of the Dunas do Rosado EPA and to the southeast of the Arrombado EPA and found a risk situation similar to that indicated by Araújo et al [59]. Aguiar et al [21] identified that flooding events can result in orders in excess of USD 147,000 and climate change scenarios show trends in increased flooding.…”
Section: Resultsmentioning
confidence: 90%
“…The geosites considered in our assessment, located in the state of Rio Grande do Norte are Ponta do Tubarão Estuarine System in the Ponta do Tubarão SDR, inventoried by Silva [21]; the geosites Falésias do Rosado, Dunas do Rosado and Falésias da Ponta do Mel, in the Dunas do Rosado EPA, inventoried by Silva [28], Terto [27], and Diniz et al [34]. In the State of Ceará, the geosites are: Sítio Retirinho, Praia de Ponta Grossa, and Praia da Redonda, in the Ponta Grossa EPA; Praia de Picos and Vila Nova, Mirante Serra do Mar, and Requenguela Beach in the Marine Life Nurseries EPA; Mirante do Icapuí and Manibu Beach, in the Barra Grande Mangrove EPA, inventoried by Araújo [26] and Diniz, Araújo and Chagas [39] (Figure 2).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Na maioria dos trabalhos desenvolvidos no Brasil para realizar os estudos acerca das inundações, não se determinou as altitudes de inundação referenciadas ao sistema de referência nacional e nem se avaliou a qualidade do produto cartográfico resultante da pesquisa, dentro das normas reguladoras da qualidade de produtos cartográficos nacionais, podendo citar os trabalhos de (Da Silva & Afonso, 2007;Saueressig, 2013;Borges et al, 2015;Prina, 2015;Reis, 2015;), por outro lado Araújo et al (2019) realizaram a calibração de um Modelo Digital de Elevação (MDE) gerado apartir do Shuttle Radar Topography Mission (SRTM) utilizando pontos de controle de terreno (GCP) vinculados ao sistema de referência e obtendo resultados satisfatórios. Já Aguiar et al (2019), utilizaram Aeronave Remotamente Pilotada (RPA -Remotely Piloted Aircraft) e pontos de controle de terreno para construção de um MDE em estudo a risco de inundação costeira. E por fim, Lima et al (2019), também utilizando pontos de controle de terreno, calibraram um MDE de um bairro urbano da Cidade de Natal-RN para identificação e avaliação de zonas de alagamento.…”
Section: Introductionunclassified